Experiences of parents of children with special needs at school entry: a mixed method approach. (20th January 2017) - Siddiqua, A.; Janus, M.
Abstract: Background: The transition from pre‐school to kindergarten can be complex for children who need special assistance due to mental or physical disabilities (children with 'special needs'). We used a convergent mixed method approach to explore parents' experiences with service provision as their children transitioned to school. Methods: Parents (including one grandparent) of 37 children aged 4 to 6 years completed measures assessing their perceptions of and satisfaction with services. Semi‐structured interviews were also conducted with 10 parents to understand their experience with services. Results: Post transition, parents reported lower perceptions of services and decreased satisfaction than pre‐transition. The following themes emerged from the qualitative data: qualities of services and service providers, communication and information transfer, parent advocacy, uncertainty about services, and contrasts and contradictions in satisfaction. The qualitative findings indicate that parents were both satisfied and concerned with aspects of the post‐transition service provision. Conclusions: While the quantitative results suggested that parents' experience with services became less positive after their children entered school, the qualitative findings illustrated the variability in parents' experiences and components of service provision that require improvements to facilitate a successful school entry.